2022
DOI: 10.1088/1361-6641/ac579d
|View full text |Cite
|
Sign up to set email alerts
|

Study of digital/analog performance parameters of misaligned gate recessed double gate junctionless field-effect-transistor for circuit level application

Abstract: In this work, the effect of gate misalignment towards the source and drain ends for 20 nm recessed double gate junctionless field-effect-transistor (R_DGJLFET) have been studied on various digital and analog performance parameters from device to circuit level while setting the simulation set-up using 2-D Silvaco ATLAS TCAD. With recessed silicon channel, the quantum confinement effects have been considered for channel thickness < 7 nm. In comparison to conventional double gate junctionless FET (C_DGJLFET), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…4 In our previous work, this issue has been addressed with a recently proposed recessed double gate JLFET (R_DGJLFET) which has shown remarkably enhanced performance with improved gate control at both device and circuit levels. [19][20][21] However, the analytical model for R_DGJLFET still needs to be developed to the best of our knowledge. Hence, in this work, we have presented an analytical model used the recently proposed R_DGJLFET operating in the subthreshold region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In our previous work, this issue has been addressed with a recently proposed recessed double gate JLFET (R_DGJLFET) which has shown remarkably enhanced performance with improved gate control at both device and circuit levels. [19][20][21] However, the analytical model for R_DGJLFET still needs to be developed to the best of our knowledge. Hence, in this work, we have presented an analytical model used the recently proposed R_DGJLFET operating in the subthreshold region.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature, it has been concluded that in the sub‐20 nm regime, the performance of JLFETs also starts degrading resulting in increased OFF‐state leakage and SCEs 4 . In our previous work, this issue has been addressed with a recently proposed recessed double gate JLFET (R_DGJLFET) which has shown remarkably enhanced performance with improved gate control at both device and circuit levels 19–21 . However, the analytical model for R_DGJLFET still needs to be developed to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%